Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If np(r-1)/a = npr/b = np(r-1)/c, show that b^2 = a(b+c)

If np(r-1)/a = npr/b = np(r-1)/c, show that b^2 = a(b+c)
 

Grade:

1 Answers

Arun
25763 Points
3 years ago
Dear suresh
 
just assume every term = k
 
Now solve this
you can clearly prove this.
 
Hope it helps
 
Regards
 
 
Arun

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free